2020
DOI: 10.1088/1742-6596/1683/4/042013
|View full text |Cite
|
Sign up to set email alerts
|

Nozzle design influence on the steam-driven ejector

Abstract: In the present paper, a series of numerical simulations of wet steam flows within ejectors distinguished by four primary nozzle contours have been carried out with the objective to evaluate the overall ejector performance. The studied primary nozzle contours are the following: a standard Laval nozzle (LAVAL); a nozzle that is designed in order to provide Constant Expansion Rate (CER); and two nozzles (MOC_SHORT, MOC_LONG) that are designed by employing axisymmetric Method of Characteristics. At first, the wet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Firstly, inside boundary layers, the function F Blend is equal to 1, which means that the function F Free becomes equal to 0. Secondly, [8]. There might be situations where values lower than Min (0.5) or higher than Max (1.0) would be appropriate for specific flows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, inside boundary layers, the function F Blend is equal to 1, which means that the function F Free becomes equal to 0. Secondly, [8]. There might be situations where values lower than Min (0.5) or higher than Max (1.0) would be appropriate for specific flows.…”
Section: Methodsmentioning
confidence: 99%
“…Figat and Piatkowska applied the GEKO model to investigate the interaction between the propeller and the fuselage of an aircraft [7]. Brezgin and Aronson adjusted the value of C SEP for the sensitivity regarding adverse pressure gradients and spreading rates, which were overpredicted by conventional models (standard k-ω, SST k-ω) [8]. Additionally, Li et al [9] compared the GEKO model with other turbulence models to investigate the influence of wall conduction on the heat transfer of supercritical n-decane in active regenerative cooling channels.…”
Section: Introductionmentioning
confidence: 99%
“…Turbulence zone LES-RANS Dissipation rate-Re 15, 000 < Re < 87, 320 [34] Transient zone GEKO Re-turbulence intensity 5, 300 < Re < 15, 000 [35] Laminar model Laminar Zone -Re < 5, 300 [36] Evaporation method Arbitrary-Lagrangian-Eulerian Droplet diameter Upperrangeddroplet < 250μmLowerrangeddroplet > 1μm [37,38] Droplet temperature Non-uniform profile Temperature gradient of droplet and ambient…”
Section: Viscous Modelsmentioning
confidence: 99%
“…Brezgin and Aronson's investigation [14] showed that varying the nozzle contours improved the ejector efficiency. Hedges and Hill [15] empirically investigated the effect of nozzle design on the flow field using two nozzles with different divergence angles.…”
Section: Introductionmentioning
confidence: 98%